Can Syzygium aromaticum and Eucalyptus globulus Ease Respiratory Infection? - PM Ridzuan; Muhammad Norfitri Md Bakim; Nur Hidayu Che Baharudin; Mohammad Asyraf Adhwa Masimen; Muhammad Faiz Zulkifli; Wan Iryani Wan Ismail (Asian Journal of Medicine & Health Sciences, 2024)
In response to the growing demand for effective treatments for respiratory infections, research has focused on the therapeutic properties of natural substances like Syzygium aromaticum (clove) and Eucalyptus globulus (Eucalyptus). Clove is rich in phytochemicals such as eugenol, which offers antimicrobial, anti-inflammatory, and antioxidant benefits in managing respiratory infections. Similarly, Eucalyptus contains eucalyptol, which is known for its antimicrobial and antiinflammatory properties. This review systematically examines research on the active constituents of clove and Eucalyptus through a detailed analysis of scientific literature from databases such as Web of Science, Scopus, Google Scholar, and Research Gate. By assessing the phytochemical and pharmacological properties of these plants, the review highlights their therapeutic potential in treating respiratory infections. It also emphasises the need to explore further their use in developing innovative treatment strategies for respiratory health.